Characterization of adolescents’ diet with the Dietary Guidelines for the Brazilian Population - Almeida Nicolau, Denise; Garcia Peloggia de Castro, Adriana (O Mundo da Saúde, 2018)
Adolescence is characterized by the transition period between childhood and adulthood. The evaluation of dietary habits at this stage provides ground for the implementation of prevention policies of chronic noncommunicable diseases. The aim of this study was to describe the eating habits of adolescent students from two technical schools in the eastern zone of the city of São Paulo and compare them with the Dietary Guidelines for the Brazilian Population. All incoming students of 2017, of both sexes, up to 19 years old and enrolled in the first year of all the Integrated Technical Courses were invited to participate. In this cross-sectional study, the total sample was 111 students. The research was conducted through an online questionnaire structured by the researcher and was developed based on the Dietary Guidelines’ 10 steps for a healthy diet. We verified that among the main meals, the most neglected by adolescents was breakfast, since it was neglected in 1 out of 4 students. Most adolescents consume less than 1 liter of water per day, do not eat whole foods, and often consume rice and beans, milk and dairy products, fruits, sweets and ultra-processed products. The eating habits of this group is not yet in line with the recommendations of the Dietary Guidelines, so a food and nutritional education work aimed at disseminating the recommendations based on this instrument is important for adopting healthier eating practices.